Regulation of nuclear factor-κB in intestinal epithelial cells in a cell model of inflammation - Fadia R. Homaidan; Iman Chakroun; Marwan E. El-sabban (Mediators of Inflammation)
Background: Interleukin-1 (IL-1), an inflammatory cytokine whose levels are elevated in inflamed mucosa, causes part of its effect on intestinal epithelial cells (IEC) through inducing ceramide production.